When living to the fullest really matters - Lim, Medha May San (2008)
Fort89 is a group of four undergraduates from Nanyang Technological University’s Wee Kim Wee School of Communication and Information. Serving as communication consultants to Assisi Hospice, we executed a strategic communication campaign from October 2006 to March 2007. The campaign, “When Living to the Fullest Really Matters”, seeks to inform and educate Assisi’s identified publics about palliative care in Singapore. With research and theoretical frameworks in place, we employed strategic communication approaches to effectively reach out to target publics and achieve our objectives. This report documents the strategy and tactics used in the campaign, as well as the limitations faced. From our campaign evaluation, we established a platform for Assisi to learn and continue such efforts in its future plans.